2012
DOI: 10.1128/aem.01525-12
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicle Formation as a Multiple-Stress Response Mechanism Enhances Pseudomonas putida DOT-T1E Cell Surface Hydrophobicity and Biofilm Formation

Abstract: ABSTRACTAmong the adaptive responses of bacteria to rapid changes in environmental conditions, those of the cell envelope are known to be the most crucial. Therefore, several mechanisms with which bacteria change their cell surface and membranes in the presence of different environmental stresses have been elucidated. Among these mechanisms, the release of outer membrane vesicles (MV) in Gram-negative bacteria has attracted particular research interest because of its involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
193
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(206 citation statements)
references
References 46 publications
9
193
1
3
Order By: Relevance
“…The different responses to changes in pH, ionic strength, and storage in the MATH assay versus filter columns show that the mechanism of adherence to hydrocarbons (in this case, hexadecane) and quartz sand is not the same and that the MATH assay cannot be used solely to predict adhesion behavior in sand. Furthermore, it was recently shown that gram-negative bacteria release membrane vesicles as a stress response changing the surface properties of the cells, including their hydrophobicity and tendency to form biofilm (Baumgarten et al 2012). Especially, the change from growth medium to various NaCl solutions (experiment 3) may have induced stress responses contributing to the nonobvious relationship between ionic strength and adhesion to quartz sand.…”
Section: Discussionmentioning
confidence: 99%
“…The different responses to changes in pH, ionic strength, and storage in the MATH assay versus filter columns show that the mechanism of adherence to hydrocarbons (in this case, hexadecane) and quartz sand is not the same and that the MATH assay cannot be used solely to predict adhesion behavior in sand. Furthermore, it was recently shown that gram-negative bacteria release membrane vesicles as a stress response changing the surface properties of the cells, including their hydrophobicity and tendency to form biofilm (Baumgarten et al 2012). Especially, the change from growth medium to various NaCl solutions (experiment 3) may have induced stress responses contributing to the nonobvious relationship between ionic strength and adhesion to quartz sand.…”
Section: Discussionmentioning
confidence: 99%
“…S1 and Table S3 in the supplemental material) in C. beijerinckii NCIMB 8052 cells grown in the presence of CaCO 3 , even though samples for protein extraction were taken at the same butanol concentration for both treated and control cultures. Finally, while several genetic and biochemical factors dictate biofilm formation, solvent stress is a positive effector (76); in this regard, it is notable that C. beijerinckii cells grown in the presence of CaCO 3 showed 5-and 2-fold decreases in levels of polysaccharide deacetylase and diguanylate cyclase, respectively (see Fig. S1 and Table S3 in the supplemental material), two enzymes that facilitate biofilm formation due to their roles in exopolysaccharide deacetylation and the generation of the bis-(3=-5=)-cyclic dimeric GMP (c-di-GMP) biofilm-signaling molecule, respectively (77).…”
Section: Discussionmentioning
confidence: 99%
“…They are also involved in the transport of metabolites, toxins, signalling molecules and other small molecules (Horstman & Kuehn, 2000Dutta et al, 2004;Keenan et al, 2008;Bomberger et al, 2009;Schertzer & Whiteley, 2012;Biller et al, 2014;Klimentová & Stulík, 2015). Furthermore, the formation of OMVs is a crucial part of the bacterial envelope stress response, protecting the bacteria from internal and external stressors (Manning & Kuehn, 2011;Baumgarten et al, 2012;MacDonald & Kuehn, 2012;Schwechheimer et al, 2013Schwechheimer et al, , 2014. In the present study, we investigated the formation of OMVs in P. putida A (ATCC 12633) in the presence of the QAC TTAB.…”
Section: Introductionmentioning
confidence: 98%